Opitz oculo-genito-laryngeal syndrome: a rare cause of recurrent aspiration pneumonia in an adult. Issue 2 (February 1998) - de Silva, D; Osborne, A; Simpson, S A; Dean, J C; Seaton, A
Abstract : A 64 year old woman presented with persistent and severe symptoms due to recurrent aspiration pneumonias associated with oesophageal reflux. She had had multiple miscarriages and her son at birth had widely spaced eyes (hypertelorism), hypospadias, bilateral undescended testes, and an imperforate anus. Her daughter has mild hypertelorism and her daughter's son had neonatal inspiratory stridor, hypospadias and hypertelorism, all features now recognised as typical of the Opitz oculo-genito-laryngeal syndrome. This syndrome is genetically heterogeneous with autosomal dominant (linked to chromosome 22q21) and X-linked (linked to Xp22) inheritance. This family's history and genetic linkage data are consistent with linkage to Xp22. The proband is a manifesting carrier of this syndrome; her history of recurrent aspiration is probably secondary to pharyngeal neuromuscular incoordination aggravating gastro-oesophageal reflux. Obtaining a family history gives a vital clue to the diagnosis of Opitz oculo-genito-laryngeal syndrome. It is also suggested that this condition should be included in the differential diagnosis of recurrent aspiration pneumonia.